Detection of ferroresonance phenomenon for the west anatolian electric power network in Turkey - EKREN, NAZMİ (UNIV ESTADUAL MARINGA, PRO-REITORIA PESQUISA POS-GRADUACAO, 2011)
Ferroresonance is an electrical phenomenon in nonlinear character, which frequently occurs in power systems containing saturable transformers and single or more-phase switching on the lines for the disjunction of the loads. In this study, the ferroresonance phenomena are considered under the modeling of the West Anatolian Electric Power Network of 380 kV in Turkey. The ferroresonance event is carried out using the switching to remove the loads at the end of the lines. In this sense, two different cases are considered. Firstly, the switching is applied at the 2nd second and the ferroresonance effects are observed between the 2nd and the 4th second of the voltage variations. As a result, the ferroresonance and non-ferroresonance cases observed before the ferroresonance, are compared with each other using the Fourier transform techniques. Hence, the properties of the ferroresonance event, which are defined between the 100 and 200 Hz, are presented in the frequency domain.
Keywords: ferroresonance; west anatolian electric power system; power system modeling; spectral analysis; feature extraction